Muçulmanos e Cristãos nos diálogos de Ramon Llull (1232-1316) - Da Costa, Ricardo (Anales del Seminario de Historia de la Filosofía, 2002)
This article intents to analyse the manner with which Ramon Llull dialogues with the muslims of his time. I will base this in his two travels to North Africa in 1293 and 1307. I will develop theme focusing on six points: 1) Historical context of the moments of his two travels and the missionary stra tegies of this time, 2) The Llullian dialogue based in his divines dignities, its similarity to the Sufis Islamic mystics hadrasand his liturgical language, which certifies the meditation and contemplation of God, 3) The desire of martyrdom in his second travel to Africa and his changing of missionary strategies, 4) The three affirmations of Llullian thought that Ramon judges possible of acceptance by Juifs and Muslims, 5) The necessity of rational proof of the existance of the Holiest Trinity and the refusal of islamic doctrine in this catholic viewpoint based in Coranic texts, 6) A short comparison between his real debates in Africa and his proposal to convert the Muslims contained in his Book of Marvels.
Keywords: Ramon Llull; Christianity; Islam; Islamic Sufis; XIII century; Coran